Evaluating the impact of a digital mapping assignment on student learning, engagement, and transferable skills - Zeedan, Rami; Bishop Simmons, Samantha; Peper, Michael (Frontiers in Education, 2026)
IntroductionResearchers examined the effectiveness of a digital mapping project created in partnership with librarians for a history course. The project centered on the Israeli–Palestinian conflict and the 1948 war, aiming to improve students’ understanding of historical context while developing transferable skills such as critical thinking, research, and technological literacy. This initiative reflects broader trends in higher education that emphasize skill development and interdisciplinary collaboration.MethodsTo evaluate the project’s impact, a mixed-methods approach was used. Data collection involved pre- and post-surveys and analysis of course assignments. The sample included 17 undergraduate students enrolled in a history course, representing diverse majors such as History, Political Science, and Education. All enrolled students participated, with no exclusion criteria applied.ResultsFindings show that the digital mapping project greatly enhanced students’ understanding of the historical context, helped develop valuable skills, and boosted engagement compared to traditional assignments. Students’ responses were mainly positive, providing useful feedback for future projects and emphasizing the potential of digital tools in college education.DiscussionThe results indicate that integrating digital humanities into history courses can create engaging learning experiences and encourage deeper student involvement. These findings add to the growing evidence supporting the use of digital tools in humanities education. However, limitations include the small sample size and dependence on self-reported data, which may impact the ability to generalize the results.